2006
DOI: 10.1016/j.chembiol.2006.07.010
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical and Genetic Approach to the Mode of Action of Fumagillin

Abstract: Previous mode of action studies identified methionine aminopeptidase 2 (MetAP-2) as the target of the antiangiogenic natural product fumagillin and its drug candidate analog, TNP-470. We report here that TNP-470-mediated MetAP-2 inhibition blocks noncanonical Wnt signaling, which plays a critical role in development, cell differentiation, and tumorigenesis. Consistent with this finding, antisense MetAP-2 morpholino oligonucleotide injection in zebrafish embryos phenocopies gastrulation defects seen in noncanon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 44 publications
2
65
0
Order By: Relevance
“…The number of vascular spaces is increased in Wnt5a-mis/overexpressing lungs, suggesting an angiogenic effect of Wnt5a, a property that has been suggested by others as well (Cheng et al, 2008;Masckauchan et al, 2006;Zhang et al, 2006), but we also show that the affected vessels are malpatterned. Results presented herein suggest that sprouting…”
Section: Discussionsupporting
confidence: 55%
“…The number of vascular spaces is increased in Wnt5a-mis/overexpressing lungs, suggesting an angiogenic effect of Wnt5a, a property that has been suggested by others as well (Cheng et al, 2008;Masckauchan et al, 2006;Zhang et al, 2006), but we also show that the affected vessels are malpatterned. Results presented herein suggest that sprouting…”
Section: Discussionsupporting
confidence: 55%
“…First, unlike the field of canonical Wnt/β-catenin signaling in which a straightforward readout system has been used to identify small molecule compounds targeting this pathway (74), the field of PCP signaling lacks a well-established pathway readout system, hindering the utilization of small molecule screening to discover compounds that specifically modulate PCP signaling for cancer therapy. Fortunately, TNP-470 was serendipitously identified as the first small molecule capable of specifically inhibiting PCP signaling (58,59). This example provides guidance for future small molecule screening for PCP signaling modulators using zebrafish high resolution phenotyping resources until a better PCP pathway readout system is developed.…”
Section: Modulation Of Pcp Signaling For Cancer Therapymentioning
confidence: 99%
“…Wnts have emerged as a novel class of angiogenic factors that promote angiogenesis, and recent evidence indicates that both Wnt/β-catenin and noncanonical Wnt signaling are involved in angiogenesis (56,57). Using a chemical genetic approach, the potent anti-angiogenic natural product fumagillin was identified as a specific inhibitor of noncanonical Wnt signaling, suggesting a link between noncanonical Wnt signaling and angiogenesis (58). Further study showed that inhibition of PCP signaling by the fumagillin analog TNP-470 disrupts endothelial cell growth, polarity, and migration.…”
Section: Role Of Pcp Signaling In Angiogenesismentioning
confidence: 99%
“…Conditional knockout (cKO) of Fgfr1 or Fgf4 and Fgf8 in the mouse mesoderm leads to axis truncation accompanied by a reduction in mesoderm differentiation (Naiche et al, 2011;Niwa et al, 2007;Wahl et al, 2007). In zebrafish, short and/or bent embryos are commonly caused by mutation or overexpression of cell signaling and adhesion genes, but the mechanics of such defects are poorly understood (Draper et al, 2001;Flowers et al, 2012;Hammerschmidt et al, 1996;Jülich et al, 2005;Kawamura et al, 2008;Keegan et al, 2002;Lele et al, 2002;Marlow et al, 2004;Okuda et al, 2010;Rauch et al, 1997a;Row and Kimelman, 2009;Shimizu et al, 2005;Stoick-Cooper et al, 2007;Tucker et al, 2008;Weidinger et al, 2005;Zhang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The non-canonical Wnt pathway establishes cell polarity, which is necessary for efficient mesoderm migration towards the dorsal midline (Roszko et al, 2009;Wallingford et al, 2002). Non-canonical Wnt signaling is also required for zebrafish trunk and tail elongation (Marlow et al, 2004;Rauch et al, 1997b;Zhang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%